Kompatibilitas Spodoptera litura Nuclear Polyhedrosis Virus (SLNPV) dengan Ekstrak Gadung Racun (Dioscorea hispida Denst) Terhadap Mortalitas Larva Spodoptera litura Fab. - Hasnah Hasnah; Susanna Susanna; Zulfikar Zulfikar (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Compatibility of Spodoptera Litura Nuclear Polyhedrosis ViruS (SlNPV) With Tropical Yam (Dioscorea hispida Denst) Ekstract on Larvae Mortality Spodoptera litura Fab.ABSTRACT. Spodoptera litura is a polyphagus and primery pest on many plants. This insect can be infected by nuclear polyhedrosis virus (NPV) and tropical yam was knowingly capable of controlling the insect. The research was aimed at finding an effective concentration of combination of SlNPV and tropical yam extract on mortality of S. litura larva. The research was conducted in Plant Pest Laboratory of Plant Pest and Disease Departemen, Agriculture Faculty, Syiah Kuala University. The experiment applied a completely randomized design (CRD), consisting of six treatments and four replications. The treatment were in SlNPV concentrations of 0, 3x105, 3x106, 3x107, 3x108, and 3x109 polyhedra inclusion body/ml respectively, combined with poisonous for gadung extract in concentration of 120 ml L-1. Data were analyzed by analysis of variance and followed by Duncan Multiple Range Test (DMRT) at level of 0,05. The result showed that application of combination of SlNPV and tropical yam extract was effective and compatible in controlling S. litura. In general, mortality of S. litura was significantly different than control. Mortality of S. litura at all treatments of concentration except S1 and S0 were 100 per cent at 9,8,8, and 7 day after application (DAA). Average of the fastest larvae mortality was 5,46 days given by 3x109 polyhedra inclusion body ml L-1 and the longest was 7,38 days given by control. Treatments of combination of SlNPV and tropical yam extract at concentration of 3x107, 3x108, and 3x109 was compatible and effective in controlling S. litura larvae with mortality level of 85,95, and 100 per cent at 7 DAA, respectively.